Acute sarcoid myopathy: a case report and literature review - Gómez-Verdú, José Miguel; Valero Cifuentes, Salvador; Pastor Quirante, Francisco; López-Andreu, Francisco Román (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Sarcoidosis is a worldwide spread disease with brad clinical spectrum, in which the pulmonary involvement is the main manifestation (more than 90% of cases); nevertheless, extrathoracic symptoms can predominate in the clinical picture and they may even be the first manifestation. One of them is the skeletal muscle involvement that normally is chronic and silent, with poor response to treatment with glucocorticoids. However, in some cases, it has an acute presentation. We present a case of a 61-year-old man with diagnosis of sarcoidosis whe were evaluated for proximal lower limb weakness within few days of evolution.